Dildora THEORY AND PRACTICE OF TRANSLATION IN LINGUISTICS: THEORY AND PRACTICE OF TRANSLATION IN LINGUISTICS - Aliqulova, Dildora (Журнал иностранных языков и лингвистики, 2022)
This article deals with different theories of translation given by theoreticians. From the very beginning, translation has performed the most important social function, making interlingual communication with people possible. According to the linguistics translation will discover itself in practice and they emphasize that translation and localization is an academic discipline that usually studies, describes and applies translation theory. Translation studies draw on many different areas that support interdisciplinary translation. These include comparative literature, history, linguistics, philology, philosophy, and others.